Engaged Soundscapes: The Emotionalized Sound of Rainer Werner Fassbinder (Cinéma & Cie. Film and Media Studies Journal, 2018)
The case study for my paper will be the late work of Rainer Werner Fassbinder, which dates from a time when the author’s concern to provoke and explore new languages was reconfigured in a more mainstream and international manner, shaping a new way of imagining popular film (Despair, Despair. Eine Reise ins Licht, 1978; The Marriage of Maria Braun, Die Ehe der Maria Braun, 1979) and television production (Berlin Alexanderplatz, WDR, 1980). In his work with a stable team of technicians (with regard to the soundtrack, musician Peer Raben, editor Juliane Lorenz, and sound engineer Milan Bor), it may reasonably be claimed that he transformed the passionate explosion of the “long 1960s” into a mature mode of production ready to enter the 1980s and beyond and to reach into our times. In this paper I will explore the experiential dimensions of the soundscapes and the music, arguing that the advent and practice of sound-mixing in the 1970s, the way in which this was used to intensify the whole audiovisual experience in film and television fiction, played an important role in reconfiguring our reflexive consciousness of social relations and political issues as individualized and emotionalized.